Correlation between Early Initiation of Breastfeeding and Exclusive Breastfeeding Success at Pagesangan Health Center, Mataram City - Nurhidayah; Wahyuningsih, Yuyu; Srihardiani; Sukardin (CV. Literasi Publikasi Indonesia, 2026)
Early Initiation of Breastfeeding (IMD) is the process of placing the baby on the mother's chest immediately after birth and allowing the baby to self-feed for at least one hour. IMD is beneficial for providing colostrum, increasing immunity, and supporting the success of exclusive breastfeeding. In Mataram City, exclusive breastfeeding coverage is still below the national target, with Pagesangan Health Center recording the lowest achievement in 2023 at 42.01%. This study aims to analyze the relationship between IMD and the success of exclusive breastfeeding at Pagesangan Health Center, Mataram City. This study used an observational analytic design with a cross-sectional approach. The population was 398 mothers with infants aged 7-12 months. A sample of 80 respondents was selected using purposive sampling. Data was collected through questionnaires and analyzed using the Chi-Square test with a 95% confidence level (α=0.05). Of the 80 respondents, 55 (68.8%) performed IMD and 50 (62.5%) successfully gave exclusive breastfeeding for up to six months. Statistical analysis showed a significant relationship between IMD and the success of exclusive breastfeeding (p=0.005; OR=7.855). IMD is significantly associated with the success of exclusive breastfeeding. Health workers need to strengthen education and support for postpartum mothers to improve IMD practices and exclusive breastfeeding coverage.